Advancing drug discovery through assay development: a survey of tool compounds within the human solute carrier superfamily - Digles, Daniela; Ingles-Prieto, Alvaro; Dvorak, Vojtech; Mocking, Tamara A. M.; Goldmann, Ulrich; Garofoli, Andrea; Homan, Evert J.; Di Silvio, Alberto; Azzollini, Lucia; Sassone, Francesca; Fogazza, Mario; Bärenz, Felix; et al. (Frontiers in Pharmacology, 2024)
With over 450 genes, Solute Carriers (SLCs) constitute the largest transporter superfamily responsible for the uptake and efflux of nutrients, metabolites, and xenobiotics in human cells. SLCs are associated with a wide variety of human diseases, including cancer, diabetes, metabolic and neurological disorders. They represent an important therapeutic target class that remains only partly exploited, as therapeutics that target SLCs are scarce. Additionally, many small molecules reported in the literature to target SLCs are poorly characterized. Both features may be due to the difficulty of developing SLC transport assays that fulfill the quality criteria for high-throughput screening. Here, we report on one of the main limitations hampering assay development within the RESOLUTE consortium: the lack of a resource providing high-quality information on SLC tool compounds. To address this, we provide a systematic annotation of tool compounds targeting SLCs. We first provide an overview on RESOLUTE assays. Next, we present a list of SLC-targeting compounds collected from the literature and public databases, and found that most lacked specificity data. Finally, we report on experimental tests of 19 selected compounds against a panel of 13 SLCs from 7 different families. Except for a few inhibitors, which were active on unrelated SLCs, the tested inhibitors demonstrated high selectivity for their reported targets. To make this knowledge easily accessible to the scientific community, we created an interactive dashboard displaying the collected data in the RESOLUTE web portal (https://re-solute.eu). We anticipate that our open-access resources on assays and compounds will support the development of future drug discovery campaigns for SLCs.